Ocorrência e bionomia de Ctenarytaina eucalypti (Maskell) (Hemiptera: Psyllidae) e seu inimigo natural Psyllaephagus pilosus Noyes (Hymenoptera: Encyrtidae) em plantas de Eucalyptus globulus - Kurylo, Cris Lisiê (2008)
Species of the genus Eucalyptus hosting several species of insects of the family Psyllidae. Among them, the specie Ctenarytaina eucalypti (Maskell) (Hemiptera: Psyllidae) is considered the most harmful, causing damage to culture wherever it has been introduced. To control these hemiptera phytophage, treatment with insecticides proved to be costly and unsustainable. But the entrance of the pest in our country, has been with their natural enemy specific Psyllaephagus pilosus Noyes (Hymenoptera: Encyrtidae). Accordingly, this study had as main objective to check the occurrence of C. eucalypti and its natural enemy P. pilosus in commercial plantations of Eucalyptus globulus; their fluctuation population; its biology and define a methodology for creation. When studied in the laboratory, the temperature of 22 ± 2°C, photoperiod of 12 hours and relative humidity of 60 ± 10% C. eucalypti completed the full cycle in 39.49 ± 6.4 days, and 8.83 ± 1.71 days for hatching eggs, and 30.67 ± 6.08 days of nymphal development, the survival of adults was on average 6,19 ± 3,06 days for males and 6,50 ± 3,88 days for females. It was found that C. eucalypti puts the eggs in the armpit of the early leaf shoots still closed. Nymphs of all instars form colonies in the shoot, leaving most of the time property with the stylus inserted in the plant. The droppings are removed in the form of bubbles or droplets that spread over the colony. The floating population was evaluated through 27 collections held fortnightly. The total of 54,160 individuals was catalogued insects. Of these, 51,119 (94.4%) were C. eucalypti, and most nymphs, total parasitoids found was 3,041, of which 73.40% corresponded to the mummies. You can see that the population of psilídeo increases when the temperatures begin to become more mild, or from the month of July. With the growth of population density of the insect-pests increases the availability of food for the parasitoid, which with its population that has increased, leading to a fall of two populations and a level of balance in a very small population level, until, according to the low level of parasitoid population, the pest again recover its population, becoming a cyclical 9 process. The longevity of P. pilosus was recorded assessing up 100 adults at a temperature of 25 ± 1°C, resulting in an average of 9.48 ± 6.37 days.